2007
DOI: 10.1007/s00464-007-9661-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric instrumentation and bacterial contamination of the peritoneal cavity

Abstract: Transgastric instrumentation does contaminate the abdominal cavity but pathogens are clinically insignificant due to species or bacterial load. Patients on PPIs do have an increased bacterial load in the gastric aspirate, with no clinical significant infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 12 publications
8
61
1
2
Order By: Relevance
“…While our data for abscess was not statistically significant, there appeared to be a trend towards higher rate of infection. Of the cultures that were positive, there was a higher rate of Gram-negative (enteric) This data supports the conclusion of several studies on rodents and humans that found an association between acid suppression and bacterial overgrowth/infection [6][7][8][9]. In a landmark study by Franklin et al, it was found that the previously held notion of a ''sterile'' foregut was challenged by the finding of polymicrobial gastric flora.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…While our data for abscess was not statistically significant, there appeared to be a trend towards higher rate of infection. Of the cultures that were positive, there was a higher rate of Gram-negative (enteric) This data supports the conclusion of several studies on rodents and humans that found an association between acid suppression and bacterial overgrowth/infection [6][7][8][9]. In a landmark study by Franklin et al, it was found that the previously held notion of a ''sterile'' foregut was challenged by the finding of polymicrobial gastric flora.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, in two retrospective human studies, the crude odds ratio for development of spontaneous bacterial peritonitis among PPI users versus nonusers ranged from 1.22 to 7.0 [8,13]. A human study by Narula et al found that transgastric instrumentation contaminates the peritoneal cavity and those patients on PPIs have a higher bacterial load compared with nonusers [7]. In this small series of 50 patients, there was no observable adverse clinical outcome as a result of a higher bacterial load; however these patients were all treated with preoperative antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The trials summarized in Table 2 suggest the rate of infectious complications could be low. Human trials investigating transgastric instrumentation of the peritoneal cavity do report contamination of the peritoneal cavity, but the contamination was found to be clinically insignificant [17,27,28] . Other adverse events including bleeding and pneumothoraces are significant complications in human thoracoscopic procedures [29,30] .…”
Section: Barriers To Clinical Practicementioning
confidence: 99%
“…Группами исследователей под руководством E. Auyang (2009), P. Nau (2010, 2011), M. Nikfarjam (2010) были анализированы серии работ, включав-ших не менее, чем 42 TGC [42,157,159,162]. P. Nau и соавт.…”
unclassified
“…Од-нако V. Narula и соавт. [157] сообщили об отсутствии интраабдоминальной инфекции после гастротомии у пациентов, перенесших диагностическую трансга-стральную лапароскопию без предварительной же-лудочной дезактивации.…”
unclassified